Homoarginine concentrations correlate with early depressive symptoms and the reduction in physical functioning within the first days after myocardial infarction - Andreas Baranyi; Andreas Meinitzer; Dirk von Lewinski; Jolana Wagner-Skacel; Sabrina Leal Garcia; Hans-Bernd Rothenhäusler; Omid Amouzadeh-Ghadikolai; Leonhard Harpf; Melanie Schweinzer; Dietmar Enko (Scientific Reports)
Abstract Early depressive symptoms within the first days after acute myocardial infarction (AMI) are mainly manifested with performance parameters (lack of energy, concentration difficulties, reduction in physical functioning). Homoarginine (hArg), a non-proteinogenic amino acid, might increase the availability of nitric oxide (NO). NO controls vasodilatation, blood flow, mitochondrial respiration and improves performance. Therefore, low plasma hArg levels after an AMI might impact performance-related early depressive symptoms. This longitudinal study aims to determine the course of plasma hArg concentrations immediately, on the fourth day and 6 months after AMI and investigates the associations between hArg and early depressive symptoms. A decrease in hArg levels, as observed in AMI patients on the fourth day after AMI, was independent of gender, age, body-mass-index and AMI type. After six months, hArg concentrations no longer differed significantly from baseline values. Females had lower hArg concentrations shortly after and also four days after the AMI compared to males. Within the first days after AMI HAMD-17 and BDI-II total depression scores and performance-related early depressive symptoms such as lack of energy, concentration difficulties and reduction in physical functioning correlated with low hArg concentrations.